2008
DOI: 10.1167/iovs.07-0619
|View full text |Cite
|
Sign up to set email alerts
|

Periocular Triamcinolone Enhances Intraocular Gene Expression after Delivery by Adenovirus

Abstract: A significant enhancement of intraocular transgene expression is associated with periocular pretreatment with corticosteroid. Histologic evidence of immune cell reduction in ocular tissues in corticosteroid-treated eyes implies a local immune response. Periocular treatment with corticosteroids may enhance adenovirus-mediated gene expression in the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This onset of gene expression is slower compared to adenovirus which peaks several days after the inoculation, both in the ear4 and in other tissues27. The delay in gene expression of BAAV is related to its molecular structure.…”
Section: Discussionmentioning
confidence: 89%
“…This onset of gene expression is slower compared to adenovirus which peaks several days after the inoculation, both in the ear4 and in other tissues27. The delay in gene expression of BAAV is related to its molecular structure.…”
Section: Discussionmentioning
confidence: 89%
“…Compared with adeno-associated viral (AAV) and retroviral delivery systems, adenoviral vectors, such as Ad5, clearly have many advantages. For example, adenoviral vectors have broad tropism allowing efficient targeting on many tissues of interest, a large payload capacity and high transduction efficiency relative to AAV system [10] and also a non-integrating characteristics which otherwise induce the risk of random mutagenesis of genome [10], [36] [36], [37], [38]. Moreover, adenoviral vectors can be engineered to cancer-selective oncolytic viruses [39], [40], [41], which are critical for clinical application of cancer gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We found that subcutaneous Nutlin-3 injection in the nape revealed a modest (27.4%), but statistically significant, reduction (P < 0.05) in the amount of retinal vessels compared with those in sham-injected mice ( Figure 7, B and C). In an attempt to reduce systemic toxicity and improve delivery to the eye, we performed similar experiments and injected Nutlin-3 in the periorbital area under the fused eyelid (15). In these experiments, we found 43.8% fewer blood vessels compared with those in the sham-injected mice (P < 0.01) (Figure 7, D and E).…”
Section: Resultsmentioning
confidence: 90%